Simulasi pengaruh pencampuran pada reaksi parallel dalam reaktor alir tangki berpengaduk - Ling Ling; Ali Altway; Sugeng Winardi (Jurnal Teknik Kimia Indonesia, 2004)
The performance of continuousstirred tank reactor was affected by both macrommng and micromixing phenomena. The effect of micromixing becomes very importantfor fast chemical rections occuring in the reactor. However, there is not enough information about the effect on the reactor performance. Previous workers have analyzed the effect of micromixing phenomena using several models. However these models can not simulate the effect of some geometries aspects of the continuous stirred tank reactor such as feed and outflow position. There for the aim of this work is to study theoretically the effect of reactor geometry on the course of two competitive fast parallel chemical reactions. The liquid height in the tank equal with the diameter. The reaction system investigated was the same as that studied by Baldyga (2001), neutralization of sodium hydroxide and hydrolysis oh ethyl chloroacetate. This work studied the effect of impeller rotation speed, mean residence time, the position of inlet  and outlet pipe, and the impeller type. The simulation was carried out using Generalized Finite Rate Formulation (GFRF) for reactive hydrodynamic system, Standard turbulent model Probability Density Function (PDF), and a mechanistic model, Packet Diffusion Model, and MRF approach to handle impeller problem. CFD commercial code FLUENT 6.0 has been used to do the simulation work. The simulation results showed that the reaction yield was affected in complicated manner by several factors such as: energy dissipation rate, pipe inlet and outlet, flow pattern, reaction zone and mean residence time. Keywords: Micromixing, Continuous Stirred Tank Reactor, CFD, Competitive Parallel Reactions AbstrakKinerja reaktor kimia tangki berpengaduk dipengaruhi baik oleh fenomena macromixing maupun micromixing. Pengaruh fenomena micromixing menjadi sangat penting untuk reaksi-reaksi cepat yang terjadi di dalam reaktor. Belum banyak informasi yang tersedia mengenai pengaruh fenomena micromixing terhadap kinerja reaktor. Beberapa penelitian terdahulu telah menganalisa secara teoritis pengaruh fenomena ini terhadap kinerja reaktor tangki teraduk dengan menggunakan beberapa model. Model - model ini belum dapat melibatkan pengaruh beberapa aspek geometri, seperti posisi aliran umpan dan posisi aliran keluar, terhadap kinerja reaktor tangki teraduk yang dioprasikan secara kontinyu. Penelitian ini bertujuan untuk mempelajari pengaruh geometri reaktor terhadap distribusi dan konversi produk dari reaksi parallel melalui teknik simulasi. Sistem yang digunakan adalah  tangki silindris berdasar datar yang dilengkapi dengan 4 buah bajjle dengan ukuran T (diameter tangki) = 0,3 m dan H (tinggi cairan) = T. Reaksi parallel kompetitif yang dipelajari adalah reaksifase cair antara asam klorida dengan natrium hidroksida dan reaksi antara elit kloroasetat dengan natrium hidroksida. Reaksi pertama jauh lebih cepat dari reaksi kedua. Sedangkan variabel percobaan yang dipelajari meliputi kecepatan putar impeller, waktu tinggal, letak masukan reaktor, letak keluaran reaktor danjenis impeller. Simulasi modeljisik yang terlibat adalah model umum formula reaksi kimia dan model aliran turbulen k-0 standar. Hasil simulasi menunjukkan bahwa selektivitas reaksi dipengaruhi secara kompleks oleh beberapa faktor yaitu energi dissipasi, posisi masukan dan keluaran rekator, pola aliran, luas daerah reaksi serta lamanya waktu tinggal. Kata Kunci: Micromixing, Reaktor Alir Tangki Berpengaduk, CFD, dan Reaksi Parallel KompetitifTheperformanceofcontinuousstirredtankreactorwasaffectedbybothmacrommngandmicromixingphenomena.Theeffectofmicromixingbecomesveryimportantforfastchemicalrections occuringinthereactor.However,thereisnotenoughinformationabouttheeffectonthereactor performance.Previousworkershaveanalyzedtheeffectofmicromixingphenomenausingseveralmodels.Howeverthesemodelscannotsimulatetheeffectofsomegeometriesaspectsofthecontinuousstirredtankreactorsuchasfeedandoutflowposition.Therefortheaimofthisworkistostudytheoreticallytheeffectofreactorgeometryonthecourseoftwocompetitivefastparallelchemicalreactions.Theliquidheightinthetankequalwiththediameter.ThereactionsysteminvestigatedwasthesameasthatstudiedbyBaldyga(2001),neutralizationofsodiumhydroxide andhydrolysisohethylchloroacetate.Thisworkstudiedtheeffectofimpellerrotationspeed,meanresidencetime,thepositionof inlet  andoutletpipe,andtheimpellertype.ThesimulationwascarriedoutusingGeneralized FiniteRateFormulation(GFRF)forreactivehydrodynamicsystem,.... StandardturbulentmodelProbabilityDensityFunction(PDF),andamechanisticmodel,PacketDiffusion Model,andMRFapproachtohandleimpellerproblem.CFDcommercialcodeFLUENT6.0hasbeenusedtodothesimulationwork.Thesimulationresultsshowedthatthereactionyieldwasaffectedincomplicatedmannerbyseveralfactorssuchas:energydissipationrate,pipeinletandoutlet,flowpattern,reactionzoneandmeanresidencetime. Keywords:Micromixing,ContinuousStirredTankReactor,CFD,CompetitiveParallelReactions